The Influence of Ultraviolet-C Light Pretreatment on Blackcurrant (Ribes nigrum) Quality During Storage - Zhuoyu Wang; Andrej Svyantek; Zachariah Miller; Haydon Davis; Ashley Kapus (Applied Sciences)
Blackcurrant is a notable superfruit in Europe, and its vitamin C content surpasses the well-known blueberry superfruit. However, due to its short shelf life during storage, consumption is mainly accounted by frozen berries, extracts, and concentrates. This study applied an intensity of 1.2 W/m2 UVC with different durations, including control (non-treated), UVC irradiation for 0.5 h (0.5 h treatment), UVC irradiation for 1 h (1 h treatment), and UVC pretreatment for 2 h (2 h treatment) to blackcurrant berries before storage. Fundamental physical (firmness and weight loss) and physicochemical characteristics (SSC, pH, and acids), microbial population changes, total phenolic content, antioxidant capacity, and specific phenolic compound changes were evaluated every five days over a twenty-day storage period. The results indicated that the longer the UVC pretreatment, the lower the water weight losses during storage. Meanwhile, the UVC pretreatment significantly affected the blackcurrant soluble solid content, resulting in higher soluble solid contents detected in the blackcurrants with the higher doses of UVC. For the mold population control, UVC effects were highly correlated with the pretreatment duration. However, UVC did not have a significant influence on the berry pH and acid contents, but the storage length slightly increased the pH and decreased the acids. At the same time, UVC pretreatment did not affect the berry firmness, polyphenols, ascorbic acid content, or antioxidant capacities, which were primarily influenced by the storage duration. The monophenolic compounds detected before and after storage indicated that more than one hour of UVC radiation influenced most of the phenolic contents largely before storage. The UVC pretreatment has also influenced some phenolic compounds. After storage, half an hour of UVC pretreatment increased cyanidin levels, and two hours of UVC pretreatment increased catechin and epicatechin levels. However, most of the compounds remained at similar amounts during storage in each treatment. Further research is needed to improve the UVC radiation time length or intensity or explore other technology combinations to optimize UVC pretreatments for blackcurrant storage.